PLANTS, POSTCOLONIALISM, AND GLOBALIZATION: ECONOMIC DIMENSIONS OF BOTANICAL EXCHANGE IN CONTEMPORARY MARKETS - Mali, Sheetal Rakesh Bhai; Bhakkd, Mamta (International Journal of Research -GRANTHAALAYAH, 2025)
This research examines the complex intersections between plant commodification, postcolonial economic structures, and contemporary globalisation processes. Through critical analysis of botanical exploitation patterns from colonial periods to present-day trading networks, this study demonstrates how plants continue to function as significant economic and cultural capital across global markets. Using a political ecology framework, the research analyses three illustrative case studies—coffee, rubber, and quinoa—to reveal how historical extraction patterns persist in modified forms while simultaneously creating spaces for resistance and economic reclamation. The study contributes to emerging scholarship by documenting how botanical economies both perpetuate historical inequities and generate opportunities for indigenous communities to assert economic sovereignty over plant resources. This work furthers understanding of plant-human relationships within global economic systems while highlighting pathways toward more equitable botanical exchange.